2022
DOI: 10.1007/s42690-022-00888-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some bee bread quality on protein content and antioxidant system of honeybee workers

Abstract: Protein content and antioxidants in both bee bread and honeybee workers were analyzed investigating the relationships between those two parameters. Results indicated significant differences between both protein and antioxidant content [total antioxidant content (TAX), glutathione (GSH) and lipid peroxidation (LPO) levels] of bee bread types. Generally, workers fed sugar syrup only (control) had significantly lower protein content, superoxide dismutase (SOD), catalase (CAT), and GSH in comparison to bees fed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Proteins with masses of approximately 90, 80, 37, 34, and 26 kDa were previously identified in the water-soluble fraction of bee bread [38]. Bands corresponding to proteins with this mass range were also previously observed for bee bread samples of various botanical origins [39]. Proteins with lower molecular weights are probably proteins of plant origin, not present in rapeseed honey.…”
Section: Protein Content and Sds Page Analysismentioning
confidence: 61%
“…Proteins with masses of approximately 90, 80, 37, 34, and 26 kDa were previously identified in the water-soluble fraction of bee bread [38]. Bands corresponding to proteins with this mass range were also previously observed for bee bread samples of various botanical origins [39]. Proteins with lower molecular weights are probably proteins of plant origin, not present in rapeseed honey.…”
Section: Protein Content and Sds Page Analysismentioning
confidence: 61%
“…The higher intensity of the bands in the paths corresponding to the natural bee bread suggests a higher protein content in these samples. Literature data report similar protein profiles for both bee pollen and bee bread with a predominant fraction of proteins between 20 and 85 kDa [30,31]. These are most likely proteins of plant origin, typical of pollens of various plant species.…”
Section: Sds-page Electrophoresismentioning
confidence: 66%
“…These are most likely proteins of plant origin, typical of pollens of various plant species. Another study has shown that regardless of the source of pollen, the protein composition of natural bee bread is conservative [31].…”
Section: Sds-page Electrophoresismentioning
confidence: 99%
“…Still, even if the phenolic acids and flavonoids are the primary compounds to determine antioxidant activity, other biomolecules can influence this (stilbenoids, sesquiterpenes, carotenoids, proteins, etc.) [74][75][76][77][78][79]. The antioxidant activity of BBE (corresponding to the TEAC method) had values ranging from 0.02 ± 0.005 to 0.07 ± 0.020 mmol Trolox/g BB.…”
Section: Ftir Spectroscopymentioning
confidence: 99%